Функція дихання в роботі над удосконаленням вокальної техніки - Карпов, В.В. (Культура народов Причерноморья, 2013)
Стаття присвячена проблемам музичної педагогіки, пов’язаним з оволодінням співочою технікою,
насамперед з тренуванням належного дихання, яке за всієї вагомості інших компонентів співу має в ньому
фундаментальне значення, а відтак має безпосередній стосунок до виразності вокального виконання. Без
належного дихання, без оволодіння навиками його використання в співі немислима підготовка професійного
вокаліста.
Дослідник підкреслює, що правильне дихання є основою оволодіння іншими елементами вокальної техніки. Статья посвящена проблемам музыкальной педагогики, связанным с овладением певческой
техникой, прежде всего с тренировкой надлежащего дыхания, которое при всей важности иных компонентов
пения имеет в нем фундаментальное значение, а следовательно непосредственно связано с выразительностью
вокального исполнения. Без надлежащего дыхания, без овладения навыками его использования в пении
немыслима подготовка профессионального вокалиста.
Исследователь подчеркивает, что правильное дыхание является основой овладения иными элементами
вокальной техники. The article is devoted to the problems of the musical pedagogic connected with the possessing of singing
technique, first of all with a training of breathing. The correct breathing beyond an importance of other components of
singing plays here a fundamental role and therefore it is closely connected with the expressiveness of the vocal
performance. The process of preparation of a professional vocalist is impossible without an educating of correct
breathing, without a possessing of a special habit in this meaning.
The researcher lays stress on the importance of right breathing and writes that the possessing of it makes the basis to
improvement of the other elements in vocal technique.
The author of the article leans upon the works by V. A. Bagadurov, B. O. Bazilikut, L. V. Dmitriyev, U. Y. Yutsevich and
other researches and musical pedagogues. But he previously uses here his own experience as the professor in Crimean
University of Culture, Art and Tourism (Simferopol), in Crimean Humanitarian University (Yalta) as well as the leading
actor and singer in Crimean Academic Ukrainian Musical Theatre.